Correção com os pares: os efeitos do processo da correção dialogada na aprendizagem da escrita em língua inglesa - Francisco Jose Quaresma de Figueiredo (2001)
In this study, we investigate the text correction strategy for written English known as peer correction. Our aim was to better understand this kind of dialogical correction and to verify its influence on the learning of English, as well as to investigate students perception of their participation in these kinds of correction activities.Ten 5 th year students who take English as a major at the Universidade Federal de Goiás took part in this case study. The principles of the qualitative research method were adopted to collect and to analyze the data, but quantitative analyses were used too.We used, as the basis for this study, theories about second language writing, error and correction. We also used, as a way to comprehend the peer correction activities, sociocultural theory and theories about collaborative learning. These theories assume that learning is facilitated through interaction and collaboration.Taking that assumption into account, we demonstrate, through data analysis, that not only do the peer correction activities promote some improvements in the written texts, but they also make the students become more motivated and confident as they realize that they are able to help each other correct the errors in their texts. They also become moremotivated as they start perceiving correction as a way of learning and not as a kind of punishment.We believe that, from the understanding of peer correction activities, we can develop second language teaching and learning practices in which students, through interaction and collaboration with peers, become more confident, motivated and reflexive.